2004
DOI: 10.1677/joe.1.05620
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of HIV-1 protease inhibitors on insulin secretion and insulin signaling in INS-1 beta cells

Abstract: The mechanism by which chronic treatment with HIV (human immunodeficiency virus)-1 protease inhibitors leads to a deterioration of glucose metabolism appears to involve insulin resistance, and may also involve impaired insulin secretion. Here we investigated the long-term effects of HIV-1 protease inhibitors on glucose-stimulated insulin secretion from beta cells and explored whether altered insulin secretion might be related to altered insulin signaling. INS-1 cells were incubated for 48 h with different conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 38 publications
5
31
0
Order By: Relevance
“…Other groups have reported that nelfinavir decreases phosphorylation of Akt at S473 in cancer cell lines, but only after 1 or 3 days of incubation (26,29). In addition, other studies have shown that HIV protease inhibitors can inhibit insulin-stimulated Akt activation (26,38,39). Our study extends these observations by showing that nelfinavir reduces Akt activation in response to EGF or IGF-I, and that decreased Akt stimulation correlates with decreased receptor tyrosine kinase activation.…”
Section: Discussionsupporting
confidence: 83%
“…Other groups have reported that nelfinavir decreases phosphorylation of Akt at S473 in cancer cell lines, but only after 1 or 3 days of incubation (26,29). In addition, other studies have shown that HIV protease inhibitors can inhibit insulin-stimulated Akt activation (26,38,39). Our study extends these observations by showing that nelfinavir reduces Akt activation in response to EGF or IGF-I, and that decreased Akt stimulation correlates with decreased receptor tyrosine kinase activation.…”
Section: Discussionsupporting
confidence: 83%
“…The association between protease inhibitors and diabetes was further strengthened by studies showing that switching patients to other regimens improved the hyperglycemia and hyperlipidemia observed during use of protease inhibitor-containing regimens. Focusing almost exclusively on the role of protease inhibitors, elegant studies demonstrated the rapid development of insulin resistance and concurrent impairment of insulin secretion following exposure to these agents (4). The mechanism of insulin resistance appears to involve interference with glucose transport: photo-affinity labeling has demonstrated binding of sequences within the common peptidomimetic core of HIV protease inhibitors to the major glucose transporter (GLUT4) (5).…”
mentioning
confidence: 99%
“…In contrast to the acute effects of PIs on glucose-stimulated insulin release, more chronic exposure to PIs appears to alter insulin signaling with clear differences between PIs [30] . Whether this is the result of direct alterations on other protein targets or secondary changes following glucose transport inhibition remains to be determined.…”
Section: Glut2mentioning
confidence: 87%